Dual-solver research based on the coupling of flux reconstruction and finite volume methods - Fu, Hao; Xia, Jian; Tian, Shuling; Chen, Long (Acta mechanica, 2023)
Accurate simulation of vortex-dominated flows has been an important issue for numerical methods in computational fluid dynamics. The recently proposed dual-solver framework provides an attracting direction for complex vortex structure resolving. In current research, we develop a dual-solver fluid solving system, in which the near-body region uses traditional finite volume method for complex geometries treatment, and apply high-order flux reconstruction (FR) method in off-body region to capture the evolution of vortex structures effectively. The parallel overset grid method is adopted in mesh assembly and data exchange process between solvers. The FR solver is developed under the framework of open-source adaptive mesh refinement (AMR) library p4est, which manages h-refinement efficiently. Cartesian cell with AMR is used in FR scheme to improve solving performance. The time marching method of coupled solvers is investigated. All modules in current system are verified, respectively. In the simulations where flow is dominated by vortex, we choose NACA0015 and S76 rotor wake resolving to verify the proposed system. The results reveal that the flow solver accurately resolves the vortex, the mesh distribution with AMR is reasonable. The results confirm the efficacy of proposed dual-solver framework.